RECURRENT ORAL ULCERATION (ROU) IN MICROCYTIC HYPOCHROMIC ANEMIA (A CASE REPORT) - Astrid Marinna; Muhammad Yusri (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Anemia is a systemic disorder that manifestation in oral cavity; one of the manifestation is ulcerated lesions. It is difficult to heal and the frequency of recurrence is also high, because in anemic condition the oral mucosa susceptible to irritation.Method: This case report tells about oral mucosal ulceration with a systemic background of Microcytic Hypochromic Anemia triggered by trauma due to orthodontic appliances. Case: A 21-year-old girl with a chief complaint of multiple ulcerated lesions on the upper and lower labial mucosa. The Ulceration has suffered along her childhood. This lesion was diagnosed as Recurrent Oral Ulceration (ROU) with a systemic background of Microcytic Hypochromic Anemia. The treatment are Benzidamine Hcl mouthwash, Triamcinolone Acetonide 0.1% in ora base, Systemic prednisone, Immunomodulators, and Multivitamins.Result: Decreased recurrence rate of ulcerated lesions Conclusion: Recurrent Oral Ulceration will easily appear in anemic conditions and difficult to treat